Why the wealthy give : the culture of elite philanthropy - Ostrower, Francie (Princeton University Press, 1995)
Why the Wealthy Give offers an in-depth look at the world of elite philanthropy. Francie Ostrower focuses on the New York City area, with its high concentration of affluent donors, to explore both the motivations of individual donors and the significance of philanthropy for the culture and organization of elite groups. Why the Wealthy Give shows that elite philanthropy involves far more than writing a check. The wealthy take philanthropy and adapt it into an entire way of life that serves as a vehicle for the social and cultural life of their class. This is reflected in the widespread popularity of educational and cultural causes among donors. At the same time, Ostrower finds divergent patterns of giving that reflect alternative sources of donor identity, such as religion, ethnicity, and gender, and explains why certain kinds of donors are more or less likely to diverge from the prestige hierarchy of their class in their philanthropy.